A GUERRA DE CONQUISTA NOS TERRITÓRIOS DOS íNDIOS KAINGANG DO TIBAGI (Revista de História Regional, 2007)
The territories of the Tibagi basin river in Paraná have been always occupied by Indian populations wich protected their forests, fields and rivers from the invaders. This paper intends to present the war of conquet moved against these populations and their territories by the whites, Europeans and Brazilians until the XIX century. It started in the first decades in the XVI century, in the name of "King" (Spain and Portugal) and in the name of "God" (Jesuitical Missions) with Portuguese and Spanish expeditions crossing the regions searching for metal, slaves and a route to Paraguay and Peru. The fight was stronger in the 1600s with the establisment of the Jesuitical Missions in Guaira and with the expeditions from S. Paulo which invaded the region capturing Indians. It went on in the XVII century with the discorery of gold and diamonds in Tibagi and with the military expeditions which built up fortifications crossing the territory to reach Mato Grosso. Later, in the name of the "Brazilian Nation", with the occupation of the Tibagi basin, and with the invention of cacique's Kaingang Inhoó fields.